Frank Norris Remembered - Crisler, Jesse S. (Book collections on Project MUSE., 2013)
Frank Norris Remembered is a collection of reminiscences by Norris's contemporaries, friends, and family that illuminate the life of one of America's most popular novelists. Considering his undergraduate education spent studying art at Academie Julian in Paris and creative writing at Harvard and his journalism career reporting from the far reaches of South Africa and Cuba, it is difficult to fathom how Frank Norris also found time to compose seven novels during the course of his brief life. But despite his adventures abroad, Norris turned out novels at.